Incidental Lesions on Routine Histopathological Examination of Appendectomy Specimen - Baral, Alina; Goyal, Binita; Pun, Chin Bahadur (Journal of Bharatpur Hospital, 2025)
Background: Acute appendicitis is one of the most common causes of acute abdomen and appendectomy is the most commonly performed surgical procedure. The lifetime frequency of acute appendicitis is 8.6 % in males and 6.7 % in females. Fecalith and lymphoid hyperplasia are the usual causative factors of acute appendicitis causing intraluminal obstruction. Intestinal parasitic diseases and malignant or benign lesions are the most prevalent unusual incidental pathological findings observed in appendectomy specimens. Almost all cases present with clinical features of acute appendicitis thus a routine histopathological study is required to identify the cause of appendicitis. Unusual incidental findings must be noted and reported as it may vary the patient management as well as outcome. Methods: A cross-sectional study was performed in the Department of Pathology, College of medical sciences, Bharatpur, Nepal over a period of three years. Histopathologic data on all appendectomy specimens (total 921) with a clinical diagnosis of acute appendicitis were retrieved from the archives of department of pathology and analyzed. Mean and percentage were calculated and findings were tabulated. Results: 21 cases with incidental unusual pathology leading to acute appendicitis were identified and included in the study. Unusual lesions of the appendix comprised 2.28% (21/921) of the appendectomy specimens examined. Mean age of presentation with unusual lesion was 49 years. Male: Female ratio was 1:1. Conclusions: There are many pathologies behind acute appendicitis apart from the usual one as fecalith and lymphoid hyperplasia. Hence routine histopathological examination of appendectomy specimens is of value to discover unusual incidental pathologies that might require additional postoperative management.